1970
DOI: 10.13057/biodiv/d170109
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of Canarium plant species used by Tobelo Dalam

Abstract: Tobelo Dalam (Togutil) ethnic group has been using local plants for years; one of them is Canarium. The ethnic are nomads and live in conservation forests. Data on ethnobotanical knowledge was collected through interview technique with "work in the wood" method. There were three types of informant: main informants, key informants, and recommended informants. Main informants were chosen through purposive sampling technique while key informants and recommended informants were chosen through snowball sampling tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…Black Fruit tree belongs to the family Burseraceae which includes the well-known canary nut trees (members of the genus Canarium L.). Black Fruit differs morphologically from the common canary (Tamalene et al 2016). Its trunk can reach the height of 10-40 m with a diameter of 40-90 cm.…”
Section: Overview Of Wandamen Ethnic Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Black Fruit tree belongs to the family Burseraceae which includes the well-known canary nut trees (members of the genus Canarium L.). Black Fruit differs morphologically from the common canary (Tamalene et al 2016). Its trunk can reach the height of 10-40 m with a diameter of 40-90 cm.…”
Section: Overview Of Wandamen Ethnic Communitymentioning
confidence: 99%
“…The ethnographic data we gathered about the Wandamen community, and the ecological data we collected about the Black Fruit were classified and integrated (Martin 2001). Simple descriptive statistics in accordance with the methods employed by Monteiro et al (2006) and Tamalene et al (2016) were used to interpret the information contributed by respondents regarding the way they construct local knowledge defining pre-harvest, harvest and post-harvest stages of Black Fruit utilization.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, ethnobotany has become increasingly popular in the development of health and conservation programs around the world. Ethnobotany is essential for biodiversity conservation (Martin 1995;Cunningham 2001;Alexiades 2003;Aryal 2009;Reta 2010;Pieroni et al 2014) and to fulfill need such as food, health, and culture (Tamalene et al 2016). Ethnobotany helps people collect information on how communities traditionally use certain plants as medicinal plants, what diseases can be treated and how it can be done (Ford 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Research result shows that wild and cultivated food crops had sociocultural meaning as well as medicinal value for disease prevention. Previous researches reported that food crops were useful for medicine (Tamalene et al 2016). It is indeed that plants have an overlap use value as source of food, culture and medicine.…”
Section: Multiplicity Of Uses Including Parts Usedmentioning
confidence: 99%